Can bipolar vaporization be considered an alternative energy source in the endoscopic treatment of urethral strictures and bladder neck contracture? - Basok,Erem K. (2008)
OBJECTIVE: We evaluated the outcome of bipolar energy by using PlasmaKinetic™ cystoscope instruments in the treatment of urethral stricture and bladder neck contracture. MATERIALS AND METHODS: Twenty-two male patients with urethral stricture and five with bladder neck contracture were treated by endoscopic bipolar vaporization. The most common etiology for stricture formation was iatrogenic (85.2%) and the mean stricture length was 12.2 mm. All patients were evaluated with urethrography and uroflowmetry one month and 3 months after surgery. Urethroscopy was routinely performed at the end of the first year. Preoperative mean maximum flow rate (Q max) was 4.9 mL/s for urethral stricture and mean Q max was 3.4 mL/s for bladder neck contracture. The results were considered as "successful” in patients where re-stenosis was not identified with both urethrography and urethroscopy. Minimum follow-up was 13.8 months (range 12 to 20). RESULTS: Tissue removal was rapid, bleeding was negligible and excellent visualization was maintained throughout the vaporization of the fibrotic tissue. Postoperative mean Q max was 14.9 mL/s and the success rate was 77.3% for urethral stricture at mean follow-up time of 14.2 months. The success rate was 60% with a mean follow-up time of 12.2 months for bladder neck contracture and the mean Q max was 16.2 mL/s, postoperatively. CONCLUSIONS: The study suggests that bipolar vaporization is a safe, inexpensive and reliable procedure with good results, minimal surgical morbidity, negligible blood loss, and thus, it could be considered as a new therapeutic option for the endoscopic treatment of urethral stricture and bladder neck contracture.